The analysis of the network parameters influence on virtual distributed cluster system's performance - Аленин, О. И. (Problems of Informatization and Control, 2009)
The problems of virtual cluster systems construction which consisted of territorially-distributed nodes are considered. On the basis of the conducted experiments WAN parameters influence (such as a delay and bandwidth limit) on the productivity of such cluster systems is analyzed. Recommendations of the effective use of additional remote nodes are given